Karakteristik Alterasi dan Mineralisasi Tipe Epitermal Daerah Gunung Budheg dan Sekitarnya, Tulungagung, Jawa Timur - Ali, Rinal Khaidar; Winarno, Tri; Jamalulail, Muhammad Ainurrofiq (EKSPLORIUM, 2020)
The discovery of vuggy quartz boulders around Pojok Village, Gunung Budheg area, Tulungagung, East Java, indicates the presence of mineral deposits process in this area. This study aims to discuss detailed characteristics of alteration and mineralization as well as mineral deposits type in the study area. The research methods are field observations completed with petrography, X-ray Diffraction (XRD), and mineragraphy laboratory analysis. The rock unit in the study area consists of six lithology units, a dacitic intrusion, andesitic lava, andesitic breccia, poly-mix breccia, reef limestone, and alluvium. The study area's alteration types are profilitic alteration, argillic alteration, advanced argillic, and silicification alteration. The profilitic alteration characterized by the abundance of chlorite minerals. The argillic alteration characterized by the abundance of kaolin minerals, while the advanced argillic alteration by the presence of kaolinite and alunite minerals. The silicification alteration characterized by abundance quartz minerals. The metallic minerals dominated in the area are sulfide minerals such as covellite, chalcocite, enargite, chalcopyrite, pyrite, and jarosite. The native gold found in an association with enargite. The study area's mineral deposit system is an epithermal high sulfidation system characterized by mineralized vuggy quartz and the presence of kaolinite mineral as an alteration mineral.